Short-Range Magnetic Order at Low Temperatures, Exchange Bias, and Negative Magnetization in Undoped CuCrO2 - Boyraz, C.; Aksu, P.; Guler, A.; Oner, Y.; Fujioka, M. (Springer, 2023)
We present the electrical and magnetic properties of polycrystalline -CuCrO2 synthesized by solid-state reaction determined to be a hexagonal phase with the space group R (3) over barm. The magnetization measurements have been carried out in the temperature range of 10-400 K, up to a field of 9 T. We observed negative magnetization under a negative internal field induced by the local structural distortions due to the change in the Cr-spin configuration in the CrO6 tetrahedral. We observed the unidirectional exchange bias field, as well as the magnetization, shift along the magnetization axis at T = 10 K and T = 50 K, below and above the Neel temperature, T-N approximate to 24 K. Based on the Modified Langevin function, the magnetization analyses reveal that the local nano-size short-range magnetic ordering forms at the temperatures below the irreversibility temperature, T-irr (where the magnetic susceptibility deviates from the high-temperature Curie-Weiss behavior). The nature of the inhomogeneous magnetic state has also been investigated under different approaches such as Griffith's phase. The resistivity measurements were performed in samples with different thermal treatment conditions. It is concluded that the surface of CuCrO2 grains is metallic and magnetically disordered, but the grains inside behave as an ideal antiferromagnetic insulator at lower temperatures. The resistivity measurements were performed in samples with different thermal treatment conditions. It is concluded that the semiconductor CuCrO2 behaves as an ideal antiferromagnetic insulator at lower temperatures.
Keywords: Thermo-induced moment; VRH Mott mechanism; negative magnetization; short-range magnetic order; exchange bias; delafossites